The perception of peripersonal space in right and left brain damage hemiplegic patients - Bartolo, Angela; Carlier, Mauraine; Hassaini, Sabrina; Martin, Yves; Coello, Yann (Frontiers in Human Neuroscience, 2014)
Peripersonal space, as opposed to extrapersonal space, is the space that contains reachable objects and in which multisensory and sensorimotor integration is enhanced. Thus, the perception of peripersonal space requires combining information on the spatial properties of the environment with information on the current capacity to act. In support of this, recent studies have provided converging evidences that perceiving objects in peripersonal space activates a neural network overlapping with that subtending voluntary motor action and motor imagery. Other studies have also underlined the dominant role of the right hemisphere in motor planning and of the left hemisphere in on-line motor guiding, respectively. In the present study, we investigated the effect of a right or left hemiplegia in the perception of peripersonal space. 16 hemiplegic patients with brain damage to the left (LH) or right (RH) hemisphere and 8 matched healthy controls (HC) performed a colour discrimination, a motor imagery and a reachability judgment task. Analyses of response times and accuracy revealed no variation among the three groups in the colour discrimination task, suggesting the absence of any specific perceptual or decisional deficits in the patient groups. In contrast, the patient groups revealed longer response times in the motor imagery task when performed in reference to the hemiplegic arm (RH and LH) or to the healthy arm (RH). Moreover, RH group showed longer response times in the reachability judgement task, but only for stimuli located at the boundary of peripersonal space, which was furthermore significantly reduced in size. Considered together, these results confirm the crucial role of the motor system in motor imagery task and the perception of peripersonal space. They also revealed that right hemisphere damage has a more detrimental effect on reachability estimates, suggesting that motor planning processes contribute specifically to the perception of peripersonal space.